The History, Status and Management of Muskoxen on Banks Island - Gunn, Anne; Shank, Chris; McLean, Bruce (ARCTIC, 1991)
Historical and archaeological records suggest that muskoxen (Ovibos moschatus) were once abundant on Banks Island. They declined around the turn of the 20th century and remained at very low population levels until the 1970s. The causes of the scarcity of muskoxen are unknown, but severe freezing rains and subsequent forage unavailability likely played a role. Aerial surveys documented an increase in the estimated population size from 3800 in 1972 to 34,225 in 1989. The rapid increase in muskox numbers has been a source of concern to the local users, who view the muskoxen as detrimental to the caribou (Rangifer tarandus pearyi), which have declined in number. Since the mid-1980s, productivity of 3-year-old muskox cows and calf survival have decreased and the prevalence of parasites has increased. Our data do not allow us to distinguish between whether those changes are density-dependent population responses or the effects of the severity of winter weather. Current management focuses on monitoring the trend of population size, the condition and reproduction of the muskoxen.Key words: muskoxen, Ovibos moschatus, Banks Island, numbers, harvest, weather, population regulation Mots clés: boeuf musqué, Ovibos moschatus, île de Banks, nombres, récolte, temps, contrôe de la population